2006
DOI: 10.1042/cs20050317
|View full text |Cite
|
Sign up to set email alerts
|

Increased systemic inflammation and oxidative stress in patients with worsening congestive heart failure: improvement after short-term inotropic support

Abstract: In the present study, we evaluated circulating pro-inflammatory mediators and markers of oxidative stress in patients with decompensated CHF (congestive heart failure) and assessed whether clinical recompensation by short-term inotropic therapy influences these parameters. Patients with worsening CHF (n=29, aged 61.9+/-2.7 years), NYHA (New York Heart Association) class III-IV, and left ventricular ejection fraction of 23.7+/-1.8% were studied. Controls comprised age-matched healthy volunteers (n=15; 54.1+/-3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 46 publications
1
53
0
1
Order By: Relevance
“…Other investigators have shown markers of inflammation and oxidative stress to be increased acutely in patients with ADHF (12,13,22,23 ). MPO is an inflammatory marker of particular interest, given its availability for clinical use and the accumulating data supporting a prognostic role for MPO in patients with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigators have shown markers of inflammation and oxidative stress to be increased acutely in patients with ADHF (12,13,22,23 ). MPO is an inflammatory marker of particular interest, given its availability for clinical use and the accumulating data supporting a prognostic role for MPO in patients with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Higher MPO concentrations are also associated with an increased prevalence of severe diastolic dysfunction and right ventricular systolic dysfunction (11 ). Furthermore, plasma markers of oxidative stress are increased in acute decompensated heart failure (ADHF) (12,13 ). The purposes of this study were first to investigate the diagnostic and prognostic value of circulating MPO concentrations in patients presenting with dyspnea to the emergency department (ED) and, second, to evaluate the additive prognostic value of MPO concentration in combination with established natriuretic peptide biomarkers and measures of cardiac function.…”
mentioning
confidence: 99%
“…3 It is not known whether processes central to pathological myocardial remodeling, such as myocyte injury/loss and ECM turnover, are activated by episodes of decompensation. However, AHFS is associated with increased mechanical strain on the heart, activation of neurohormonal systems, and increased inflammation and oxidative stress, 4,5 stimuli that are known to mediate myocardial injury and ECM turnover. Therefore, it is possible that myocyte loss and ECM turnover are accelerated during episodes of AHFS.…”
Section: Clinical Perspective On P 50mentioning
confidence: 99%
“…Antiplatelet resistance and up-regulation of the COX-2 enzyme coupled with increased levels of F2-isoprostanes may lead to uncontrolled thromboxane synthesis. Such COX-1-independent mechanisms are especially relevant to patients with diabetes mellitus, hyperlipidemia, smoking and heart failure; all of which are associated with augmented lipid peroxidation of arachidonic acid and consequent overproduction of isoprostanes [38,[42][43][44][45][46][47][48][49] (Figure 3). In our recent work, 599 patients with chronic cardioand cerebrovascular diseases (355 men, mean age 64 ± 11 years; 244 women, mean age 63 ± 10 years) who were taking aspirin 100-325 mg/d were examined [28] .…”
Section: Aspirin Resistancementioning
confidence: 99%